Identification of a multiple DAMP scavenger mimicking the DAMP-binding site of TLR4 to ameliorate lethal sepsis - Murao, Takuya; Ma, Gaifeng; Murao, Atsushi; Jha, Alok; Li, Jingsong; Lee, Yongchan; Zhou, Mian; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2025)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. Current treatments are limited to source control and supportive care, underscoring the urgent need for novel therapeutic interventions. Endogenous molecules released from stressed or damaged cells, known as damage-associated molecular patterns (DAMPs), exacerbate inflammation, organ injury, and mortality in sepsis. In this study, we discovered a novel therapeutic compound, opsonic peptide 18 (OP18), designed to scavenge multiple DAMPs, including extracellular cold-inducible RNA-binding protein (eCIRP), high mobility group box 1 (HMGB1) and histone H3, by facilitating their clearance via macrophages. OP18 was developed by identifying a 15-amino acid (aa) binding site within the extracellular domain of Toll-like receptor 4 (TLR4) shared by eCIRP, HMGB1, and histone H3, then extending it with an αvβ3-integrin binding RGD (Arg-Gly-Asp) motif, resulting in an 18-aa peptide. Our data show that OP18 binds strongly to the above DAMPs and interacts with αvβ3-integrin on macrophages, promoting phagocytosis of DAMPs and facilitating their lysosomal degradation. In vitro, OP18 reduced the production of the inflammatory cytokine TNF-α in DAMP-activated macrophages and restored mitochondrial function, as evidenced by improved oxygen consumption rate (OCR) and ATP production. In a lethal sepsis model induced by cecal ligation and puncture (CLP), DAMP levels were significantly elevated, while OP18 treatment markedly reduced the serum DAMP levels. Additionally, OP18-treated septic mice demonstrated reduced blood organ injury markers, decreased proinflammatory cytokine levels, attenuated ALI, and improved survival. These findings establish OP18 as a promising therapeutic molecule that reduces DAMP-induced inflammation, offering a potential strategy to improve outcomes in lethal sepsis.